Influence of culture over marital love and fidelity in ancient Rome and Ugboha of Edo state (2013)
This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other.